Laboratory Study on Properties of Diatomite and Basalt Fiber Compound Modified Asphalt Mastic. (1st August 2017) - Cheng, Yongchun; Zhu, Chunfeng; Tan, Guojin; Lv, Zehua; Yang, Jinsheng; Ma, Jiansheng
Abstract : In order to improve the performance of asphalt mastic, some researchers have added diatomite or basalt fiber as a modifier to the asphalt mastic, and the results show that some properties of the asphalt mastic were improved. For the simultaneous addition of diatomite and basalt fiber, two kinds of modifier, compound modified asphalt mastic had not been reported; in this paper, thirteen groups of diatomite and basalt fiber (DBFCMAM) compound modified asphalt mastic with different content were prepared to study the performance. Softening point, cone penetration, viscosity, and DSR tests were conducted, for the high temperature performance evaluation of DBFCMAM, whereas force ductility and BBR tests were used in the low temperature performance study of the DBFCMAM. The results demonstrated that the high temperature performance of DBFCMAM was increased; moreover, the low temperature performance of DBFCMAM improved by diatomite and basalt fiber according to the results of the force ductility test; however, the conclusion of the BBR test data was inconsistent with the force ductility test. In summary, the high temperature and low temperature properties of DBFCMAM had been improved.